Determination of caffeine, trigonelline and chlorogenic acid by high-performance thin-layer chromatography in coffee infusions and study of the effect of these infusions on α-amylase activity - Maria Zych; Karolina Leopold; Alina Pyka-Pająk (Farmacja Polska, 2024)
Subject of study Coffee infusions are extremely popular worldwide due to their pleasant taste, ability to reduce fatigue, increase concentration and improve productivity. Infusion extracted from coffee beans are mixtures of many chemical compounds, both volatile and non-volatile. Among the non-volatile components, caffeine, trigonelline and chlorogenic acid appear to be the dominant ones. These substances are responsible for both the flavour sensations and influence on biological activities, such as mental stimulation effects or reducing the risk of type 2 diabetes. Aim of study The aim of the present study was: (I) to develop and validate a high-performance thin-layer chromatography (HPTLC) method for the simultaneous quantification of caffeine, trigonelline and chlorogenic acid in coffee bean infusions; (II) to use this method to determine caffeine, trigonelline and chlorogenic acid in green, light and dark roasted coffee bean infusions prepared both by immersion (brewing) and pressure methods; (III) to evaluate the effects of coffee infusions on α-amylase activity. Materials and methods Simultaneous determination of caffeine, trigonelline and chlorogenic acid was carried out on glass HPTLC plates coated with silica gel 60 F254 with a concentration zone and the mobile phase consisted of a mixture of: chloroform, ethyl acetate, methanol and formic acid in a volume ratio of 10:6:3:1 (v/v). After the plates were developed and dried, densitometric scanning was performed at wavelengths of 270, 275 and 330 nm for trigonelline, caffeine and chlorogenic acid, respectively. The analysis of the effect of coffee infusions on the α-amylase activity was carried out using a porcine pancreas α-amylase. Results Green coffee infusions prepared using the immersion method was proved to have the highest chlorogenic acid content, while the highest trigonelline and caffeine contents were observed in infusions also obtained using the immersion method, but from dark-roasted coffee. Infusions of green coffee and light and dark roasted coffee inhibited α-amylase activity, with green coffee infusions showed the strongest effect. Conclusions The developed method is selective, precise, accurate and sensitive, so it can be used for the simultaneous determination of caffeine, trigonelline and chlorogenic acid in heat-treated and non-heat-treated coffee bean infusions. The results of the analysis of the effect of coffee infusions on the α-amylase activity create the opportunity to use these infusions, particulary unroasted coffee infusions, in the prevention of type 2 diabetes.